Investigation of the efficacy and tolerability of Dr Michaels® (also branded as Eczitinex® and Itchinex Eczitinex®) topical products in the treatment of atopic dermatitis in children - França, K; Hercogovấ, J; Fioranelli, M; Gianfaldoni, S; Chokoeva, A A; Tchernev, G; Wollina, U; Tirant, M; Bayer, P; Coburn, M; Anderson, P; Donnelly, B; et al. (Journal of biological regulators and homeostatic agents, 2016)
Atopic eczema is a chronic relapsing inflammatory skin disorder, characterized clinically by intensely pruritic eczematous skin lesions and a defective epidermal barrier. It affects more than 15% of children and up to 10%of adults, which makes the disease a social health problem still without a challenging treatment. The aim of this study was to evaluate the efficacy and tolerability of Dr Michaels® (Eczitinex®) topical product family in the treatment of atopic dermatitis in children. We studied a group of 30 patients (17 female, 13 male), aged 5 to 13 (mean age: 9), affected by atopic dermatitis since they were newborn. All patients had been unsuccessfully treated with conventional anti-inflammatory therapies and ceased treatment 2 weeks before commencing research. The patients were treated with Dr Michaels® (Eczitinex® and Itchinex®) product family including a moisturising bar, topical ointment and PSC 900 oral herbal formulation. The treatment was evaluated clinically and photographically at 0, 1, 2, 4, 6, 8, 10, 12, and 14 weeks. Twenty-eight patients showed a significant improvement of cutaneous rashes and pruritus on the first week of treatment, with a complete remission at 10-12 weeks. Only two patients, brother and sister respectively, showed a slow response to treatment and reported an increasing itching. Following 14 weeks of treatment with the Dr Michaels® (Eczitinex® and Itchinex®) product family, patients demonstrated complete resolution of their AD. All patients showed a marked improvement in their condition within 3 days of treatment with most of the lesions and symptoms totally resolved within 10 to 12 weeks of treatment with Dr Michaels® (Eczitinex® and Itchinex®) family of products. This clinical report highlights that the Dr Michaels® (Eczitinex® and Itchinex®) product family is a safe and effective treatment option for AD.
Keywords: Dermatitis, Atopic; Humans; Phytotherapy; fytoterapie; dítě; Child; Female; kůže; Ointments; výsledek terapie; lidé; aplikace kožní; předškolní dítě; ženské pohlaví; Male; masti; Adolescent; Treatment Outcome; atopická dermatitida; Administration, Cutaneous; mužské pohlaví; Child, Preschool; Skin; mladiství